THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND MOTIVATION ON LECTURER PERFORMANCE OF PAMULANG UNIVERSITY - Duddy Dinantara, Mohamad (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
This study aims to determine the effect of organizational commitment and motivation on lecturer performance of Pamulang University. The research method used is quantitative. The number of samples used is 200 respondents with the Slovin formula, and the sample technique used is proporsionate random sampling. Analytical methods used are multiple linear regression, consist of descriptive analysis, validity test, reliability test, classical assumption test, partial test, simultaneous test and test of determination. Result of research proves organizational commitment have significant effect to lecturer performance equal to 0,485. Motivation has a positive and significant effect on lecturer's performance of 0.304. Simultaneously commitment and motivation have a significant effect on performance with contribution of 44.5%